Indonesian Translation Equivalence Of Action Verbs On Linkedin Homepage Template - Roro Shinta Felisia , Raden (International Journal of Educational Research & Social Sciences, 2023)
An online platform to find professional opportunities, LinkedIn, reaches more than 22 million Indonesian users. The Indonesian version of the LinkedIn homepage certainly plays a significant role to spread information. This study has the purpose to describe the Indonesian translation equivalence of action verbs on the LinkedIn homepage template. The result shows that the translations are: (1) formal equivalences in the form of root verbs, (2) formal equivalences in the form of root verbs plus affixes, and (3) dynamic equivalences in the form of root nouns with no mark describing amount. This study is expected to contribute to the field of translation, especially in the online platform.